The Use of Nasojejunal Nutrition in Patients with Chronic Pancreatitis - Skipworth, James Robert Anthony; Raptis, Dimitri Aristotle; Wijesuriya, Shalini; Puthucheary, Zudin; Olde Damink, Steven W M; Imber, Charles; Malagò, Massimo; Shankar, Arjun (JOP. Journal of the Pancreas, 2011)
Context Abdominal pain, malabsorption and diabetes all contribute to a negative impact upon nutritional status in chronic pancreatitis and no validated standard for the nutritional management of patients exists. Objective To assess the effect of nasojejunal nutrition in chronic pancreatitis patients. Design All consecutive chronic pancreatitis patients fed via the nasojejunal route between January 2004 and December 2007 were included in the study. Patients were assessed via retrospective review of case notes. Results Fifty-eight chronic pancreatitis patients (35 males, 23 females; median age 46 years) were included. Patients were discharged after a median of 14 days and nasojejunal nutrition continued for a median of 47 days. Forty-six patients (79.3%) reported resolution of their abdominal pain and cessation of opioid analgesia intake over the study period and median weight gain at 6 weeks following nutritional cessation was +1 kg (range -24 to +27 kg; P=0.454). Twelve (20.7%) patients reported recurrence of their pain during the follow-up period and complications were both minor and infrequent. Significant improvements were noted in most blood parameters measured, including: sodium (from 134.8 to 138.1 mEq/L; P<0.001); urea (from 3.4 to 5.1 mmol/L; P<0.001); creatinine (from 58.3 to 60.3 μmol/L; P<0.001); corrected calcium (from 2.24 to 2.35 mmol/L; P=0.018); albumin (from 34.5 to 38.7 g/L; P=0.002); CRP (from 73.0 to 25.5 mg/L; P=0.006); and haemoglobin (from 11.8 to 12.4 g/dL; P=0.036). Conclusion Nasojejunal nutrition, commenced in hospital and continued at home, is safe, efficacious and well tolerated in patients with severe chronic pancreatitis and is effective in helping to relieve pain and diminish analgesic requirements.